Developmental Psychopathology 2016
DOI: 10.1002/9781119125556.devpsy412
|View full text |Cite
|
Sign up to set email alerts
|

Interparental Conflict and Child Adjustment

Abstract: This chapter reviews empirical knowledge on the association between interparental conflict and child adjustment problems. We begin with a brief historical overview. We then deconstruct the concept of interparental conflict, describing key dimensions of incidents of such conflict (topic, behavioral tactics, emotions, and resolution) that have been linked to children's adjustment. Next, we turn to a presentation of theories on the link between interparental conflict and child adjustment problems, highlighting ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(56 citation statements)
references
References 432 publications
1
54
1
Order By: Relevance
“…Perhaps because IPA is often studied using clinical, court, law enforcement, and community agency samples, it is recognized as a more serious form for interparental discord (Jouriles et al, ) as it is a leading cause of death, particularly for women (Smith, Fowler, & Niolon, ). The World Health Organization () has indicated that violence against women is a “global health problem of epidemic proportions.” Realizing the potential serious consequences of IPA for both adults and children, the goal of this article is to bring awareness to the impact of terminology used to describe interparental conflict on research strategies, intervention development, delivery of treatment services, social policy, and legal ramification for families.…”
Section: Terminology and Primary Goals Of Two Scholarship Groupsmentioning
confidence: 99%
See 4 more Smart Citations
“…Perhaps because IPA is often studied using clinical, court, law enforcement, and community agency samples, it is recognized as a more serious form for interparental discord (Jouriles et al, ) as it is a leading cause of death, particularly for women (Smith, Fowler, & Niolon, ). The World Health Organization () has indicated that violence against women is a “global health problem of epidemic proportions.” Realizing the potential serious consequences of IPA for both adults and children, the goal of this article is to bring awareness to the impact of terminology used to describe interparental conflict on research strategies, intervention development, delivery of treatment services, social policy, and legal ramification for families.…”
Section: Terminology and Primary Goals Of Two Scholarship Groupsmentioning
confidence: 99%
“…Exposure to destructive interparental conflict has been related to a number of unfavorable outcomes for children, including internalizing and externalizing behavior problems (Cummings & Davies, 2010), cognitive impairment (Grych, Harold, & Miles, 2003), academic underachievement (McCoy, George, Cummings, & Davies, 2013), social incompetence (Lindsey, Colwell, Frabutt, & MacKinnon-Lewis, 2006), and decreased physical health (El-Sheikh, Harger, & Whitson, 2001). Additionally, with repeated exposure, children may deem destructive conflict tactics (e.g., uncontrolled emotional reactions) as appropriate and acceptable communication and conflict resolution strategies and further reinforce such behaviors in their own interpersonal relationships (Cummings, Goeke-Morey, & Papp, 2004;Grych & Fincham, 1990;Jouriles et al, 2016).…”
Section: Terminology and Primary Goals Of Two Scholarship Groups Chilmentioning
confidence: 99%
See 3 more Smart Citations